FNR Regulates the Expression of Important Virulence Factors Contributing to the Pathogenicity of Avian Pathogenic Escherichia coli - Barbieri, Nicolle L.; Vande Vorde, Jessica A.; Baker, Alison R.; Horn, Fabiana; Li, Ganwu; Logue, Catherine M.; Nolan, Lisa K. (Frontiers in Cellular and Infection Microbiology, 2017)
Avian pathogenic Escherichia coli (APEC) is the etiologic agent of colibacillosis, an important cause of morbidity and mortality in poultry. Though many virulence factors associated with APEC pathogenicity are known, their regulation remains unclear. FNR (fumarate and nitrate reduction) is a well-known global regulator that works as an oxygen sensor and has previously been described as a virulence regulator in bacterial pathogens. The goal of this study was to examine the role of FNR in the regulation of APEC virulence factors, such as Type I fimbriae, and processes such as adherence and invasion, type VI secretion, survival during oxidative stress, and growth in iron-restricted environments. To accomplish this goal, APEC O1, a well characterized, highly virulent and fully sequenced strain of APEC harboring multiple virulence mechanisms, some of which are plasmid-linked, was compared to its FNR mutant for expression of various virulence traits. Deletion of FNR was found to affect APEC O1’s adherence, invasion and expression of ompT, a plasmid-encoded outer membrane protein, type I fimbriae, and aatA, encoding an autotransporter. Indeed, the fnr- mutant showed an 8-fold reduction in expression of type I fimbriae and a highly significant (P<0.0001) reduction in expression of fimA, ompT (plasmid-borne) and aatA. FNR was also found to regulate expression of the type VI secretion system, affecting the expression of vgrG. Further, FNR was found to be important to APEC O1’s growth in iron-deficient media and survival during oxidative stress with the mutant showing a 4-fold decrease in tolerance to oxidative stress, as compared to the wild type. Thus, our results suggest that FNR functions as an important regulator of APEC virulence.